A comparabilidade das demonstrações financeiras e seus efeitos nos Cash Holdings das empresas brasileiras - Narciso, Laís Franca (2019)
Financial statement’s users decision making usually involve a choice between alternatives. Thus, information about an entity is more useful if it can be easily compared with similar information reported by other entities or by the same entity in other periods. Comparability is the qualitative characteristic that enables users to identify and understand similarities and differences among items. Empirical studies provided evidence that comparability can assist in reducing the informational asymmetry and improve access to external financing. Since the access to external financing is an important determinant of the corporate cash holdings, the purpose of this study is to investigate the effects of financial statement comparability on cash holdings of Brazilian listed firms during the period from 2007 to 2017. Comparability was calculated using the De Franco, Kothari and Verdi (2011) model, its relationship with the cash holdings was analyzed using panel data regression. It was found a positive and significant effect of the comparability on the corporate cash holdings, indicating that firms with greater comparability maintain more cash. Then it was also analyzed the interaction (multiplicative effect) of comparability with financial constraints and with corporate governance on the corporate cash holdings. The evidence doesn’t show significant effects of financial constraints nor its interaction with comparability on corporate cash holdings. On the corporate governance model, the interaction exhibits a positive and significant effect on cash holdings. Indicating that on the firms with good governance, comparability has a positive effect on the corporate cash holdings.